The handbook of energy trading - Fiorenzani, Stefano; Ravelli, Samuele; Edoli, Enrico (Chichester, West Sussex, U.K. ; Hoboken, N.J. : Wiley, 2012)
"This book guides readers through all the various aspects of energy trading from operational strategies and mathematical methods to practical techniques, providing support for energy trading managers, energy traders and energy trading analysts"--
Energy markets as efficient markets -- Directional trading -- Spread trading -- Options and non-linear derivatives -- Structured products on energy -- Metatrading strategies and capital allocation techniques.
Includes bibliographical references and index.
Print version record.
Keywords: Energy industries; Power resources; Commodity exchanges; TECHNOLOGY & ENGINEERING -- Power Resources -- Nuclear; Commodity exchanges; Energy industries; Power resources; Electronic books